Pengaruh Volume Usaha dan Harga Pokok Penjualan Terhadap Sisa Hasil Usaha (SHU) Pada Koperasi Karyawan PT Sarandi - Nurohmah, Kiki (Universitas Prof.Hazairin,SH Bengkulu, 2022)
ABSTRACT This study aims to determine the effect of business volume and cost of goods sold on the remaining operating results. The variables used in this study are business volume, cost of goods sold and the remaining operating results. This research was conducted at the Employee Cooperative of PT Sarandi in 2016 - 2021. The research method used was a quantitative method with an associative approach. The sampling technique used in this study is non-probability sampling with a total/census sampling technique. The data analysis used is parametric with multiple linear analysis. The results of the study of business volume have a positive effect on the remaining operating results with a significance of 0.000 <0.05 and tcount > ttable (47.009 > 1.99495). Cost of goods sold has a negative effect on the remaining operating results with a significance of 0.000 <0.05 and tcount > ttable (43.156 > 1.99495). And business volume and cost of goods sold have a simultaneous effect on the remaining operating results with a significance of 0.000 < 0.05 and Fcount > Ftable (1107,045 > 3,13). The contribution of the variable of operating volume and cost of goods sold to the remaining operating results is 97%. Keywords: Business Volume, Cost of Goods Sold, Remaining Operating Income